2012
DOI: 10.1177/1350650112458873
|View full text |Cite
|
Sign up to set email alerts
|

Dicationic ionic liquids as lubricants

Abstract: Twelve dicationic ionic liquids have been investigated for their potential inlubricants. The dications selected were synthesized from oligoethylene glycols linking two cationic moieties based on either N-methylimidazolium or N-methylpyrrolidinium at the extremities. As anions, chloride, bis(trifluoromethanesulfonyl)imide (Tf2N), methanesulfonate and butansulfonate were chosen. Thermal stability of the IL has been evaluated by thermogravimetric analysis and differential scanning calorimetry showing good propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
(25 reference statements)
0
22
0
2
Order By: Relevance
“…On the other hand, anion influence on tribological properties of ionic liquids were already demonstrated by Kronberger et al [21], with similar trends detected for ionic liquids containing RSO À 4 , and NTf À 2 anions, as well as Pagano et al [13], who detected the presence of a tribolayer of inorganic fluoride by XPS, generated from NTf À 2 anion, being responsible for the good performance. Additionally, [C 1 Py(CH 2 OCH 2 ) 3 (10), where noticeable reduction of COF (0.099), even with an addition of 0.25% of IL, was observed.…”
Section: Neat Ionic Liquidsmentioning
confidence: 54%
See 2 more Smart Citations
“…On the other hand, anion influence on tribological properties of ionic liquids were already demonstrated by Kronberger et al [21], with similar trends detected for ionic liquids containing RSO À 4 , and NTf À 2 anions, as well as Pagano et al [13], who detected the presence of a tribolayer of inorganic fluoride by XPS, generated from NTf À 2 anion, being responsible for the good performance. Additionally, [C 1 Py(CH 2 OCH 2 ) 3 (10), where noticeable reduction of COF (0.099), even with an addition of 0.25% of IL, was observed.…”
Section: Neat Ionic Liquidsmentioning
confidence: 54%
“…Previous works on the use of DILs derived from imidazolium [11,12] and pyrrolidinium [13] for lubrication have shown very promising results. Nevertheless, to our knowledge, no papers were published about using pyridinium DILs as lubricants or lubricant additives.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The structures of the dicationic IL (IL2-di) and its monocationic analogue (IL2), which was used as a benchmark in this study, are shown in Figure 1. connecting chain [28][29][30][31] that was associated with better tribological properties, higher stability, lower toxicity and corrosiveness of the dicationic ILs [14,[31][32][33][34][35][36][37][38][39][40][41]. In the literature, there is a consensus of opinions that the good friction-reduction and wearresistant properties of ILs are owed to their ability to form stable adsorbed layers and protective tribofilms [4,27,[42][43][44].…”
Section: Methodsmentioning
confidence: 99%
“…Another approach relies on bridging two cationic head groups by PEG chain. Molecular dynamics simulation and advanced spectroscopy have revealed significant differences in structural heterogeneity and nano-organization between monocationic and geminal dicationic ILs with a long connecting chain [28][29][30][31] that was associated with better tribological properties, higher stability, lower toxicity and corrosiveness of the dicationic ILs [14,[31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%